Religious Education in Greece: a new Curriculum, an old issue - Koukounaras-Liagkis, M. (British Journal of Religious Education, 2015)
Religious Education (RE) in Greece is a compulsory school subject according the 2011 new framework for compulsory education, entitled ‘New School’. This article focuses on two statutory documents for RE, ‘The Curriculum for RE’ and the ‘The Teacher’s Guide for RE’, and the pilot scheme of the new curriculum running in school years, 2011–2014, in 188 schools (primary and secondary education). Findings of the research demonstrate that, though the revision seems inevitable, the pedagogical and theological dimension of the RE curriculum is radical as it is based on contemporary theories and methodologies of the construction of the curriculum and RE approaches. However, the article indicates constructivist and critical approaches to RE that influenced the change to an actual non-confessional compulsory subject and also highlighted the tension between an overall constructivist approach to learning and the traditional orthodox content of much of the curriculum. The author opens a discussion on problematic aspects that need to be taken in to consideration when revising the curriculum.